Perubahan Sosial Budaya Masyarakat Arab Jahiliyyah (Ditinjau Dari Fiqhalhadits) - Nasrun, Mahdalena (Al Mabhats : Jurnal Penelitian Sosial Agama, 2016)
Social and cultural life Arab jahiliyyah society changed through the process of diffusion. This means that Muhammad SAW brought Islam started preaching of those nearby and continues to others. On the name of religion, the changing social and cultural life of the society in this case is not differentiated between the period of Mecca and Medina. The question iswhat isthe purpose of thesocio-cultural changes? howsocial and cultural changes in Arab jahiliyah society reviewed fiqhal-Hadith?. The results ofthis study; First, socio-culture is the product ofthought, emotion and human initiativein full of their need sandlargely followed thepractice that has been done ancestors. Second,social and cultural lifeof Arab jahiliyah society contained inthe hadithis classified, among others; language, knowledge systems, socialorganization, equipment of life systemsandtechnology, livelihoodsystems, the religious, and the arts. Social and culturallife of theArabjahiliyah society is omitted, repaired, maintained and thereis new.